Readiness for Marriage Among Young Adults: A Review from the Perspective of Parental Attachment - Rohmawati, Devy Nur; Hanifah, Fikrotul (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Changes in the mindset of the current generation have the potential to influence individuals' decisions to marry, making readiness for marriage an important aspect to consider. One factor that plays a role in readiness for marriage is the relationship between individuals and their parents (parental attachment). This study aims to determine the relationship between parental attachment and readiness for marriage in early adulthood. The research subjects consisted of 319 young adults selected using purposive sampling. The research method used was quantitative correlational with analysis using correlation tests. The results showed that there was no significant relationship between parental attachment and readiness for marriage, with a significance value of 0.753 and a very weak relationship strength (r = 0.018). These findings indicate that the level of parental attachment does not directly affect the readiness for marriage in young adults.Perubahan pola pikir pada generasi masa kini berpotensi memengaruhi keputusan individu untuk menikah, sehingga kesiapan menikah menjadi aspek penting yang perlu diperhatikan. Salah satu faktor yang berperan dalam kesiapan menikah adalah hubungan antara individu dengan orang tua (parental attachment). Penelitian ini bertujuan untuk mengetahui hubungan antara parental attachment dengan kesiapan menikah pada dewasa awal. Subjek penelitian berjumlah 319 orang dewasa awal yang dipilih menggunakan teknik purposive sampling. Metode penelitian yang digunakan adalah kuantitatif korelasional dengan analisis menggunakan uji korelasi. Hasil penelitian menunjukkan bahwa tidak terdapat hubungan yang signifikan antara parental attachment dengan kesiapan menikah, dengan nilai signifikansi sebesar 0.753 dan kekuatan hubungan yang sangat lemah (r = 0.018). Temuan ini menunjukkan bahwa tingkat parental attachment tidak berpengaruh secara langsung terhadap kesiapan menikah pada individu dewasa awal.